Grip and Sliding Friction Processes (Eurasian Journal of Engineering and Technology, 2022)
This article discusses the processes of adhesion and sliding friction. However, due to the extreme complexity of this physical and mechanical phenomenon and the difficulty of assessing numerous factors, influencing him, the exact general laws of friction have not yet been established. If necessary, it can be determined empirically and through approximate calculations